Share price performance following actual share repurchases - Zhang, Hua (Journal of Banking & Finance, 2005)
Using unique actual daily share repurchase data from Hong Kong, this paper investigates share price performance surrounding and following actual share repurchases. It is found that repurchasing firms buy back shares following price drops, suggesting that they behave opportunistically when implementing actual share repurchases. On average, the initial 3-day market response to actual repurchases is about 0.43%. Repurchasing firms do not seem to exhibit superior abnormal performance over long horizons when they make actual share repurchases. However, the price performance of repurchasing firms varies across firm size and market–book value ratios, and shows a clear and consistent pattern. The market responds the most favorably to repurchases that are made by small and value (high book-to-market value) firms. Over a long horizon, there is some evidence that repurchases made by value firms show superior performance. The three-year buy-and-hold abnormal return, which is measured against a portfolio of control firms that are matched by size and book-to-market value ratios, is over 20%. At least, repurchases made by high book-to-market value firms, for which undervaluation is more likely to occur, can benefit long-term shareholders.